An insight into the neuroprotective and anti-neuroinflammatory effects and mechanisms of Moringa oleifera - Azlan, Ummi Kalthum; Khairul Annuar, Nur Aisyah; Mediani, Ahmed; Aizat, Wan Mohd; Damanhuri, Hanafi Ahmad; Tong, Xiaohui; Yanagisawa, Daijiro; Tooyama, Ikuo; Wan Ngah, Wan Zurinah; Jantan, Ibrahim; Hamezah, Hamizah Shahirah (Frontiers in Pharmacology, 2023)
Neurodegenerative diseases (NDs) are sporadic maladies that affect patients’ lives with progressive neurological disabilities and reduced quality of life. Neuroinflammation and oxidative reaction are among the pivotal factors for neurodegenerative conditions, contributing to the progression of NDs, such as Parkinson's disease (PD), Alzheimer's disease (AD), multiple sclerosis (MS) and Huntington’s disease (HD). Management of NDs is still less than optimum due to its wide range of causative factors and influences, such as lifestyle, genetic variants, and environmental aspects. The neuroprotective and anti-neuroinflammatory activities of Moringa oleifera have been documented in numerous studies due to its richness of phytochemicals with antioxidant and anti-inflammatory properties. This review highlights up-to-date research findings on the anti-neuroinflammatory and neuroprotective effects of M. oleifera, including mechanisms against NDs. The information was gathered from databases, which include Scopus, Science Direct, Ovid-MEDLINE, Springer, and Elsevier. Neuroprotective effects of M. oleifera were mainly assessed by using the crude extracts in in vitro and in vivo experiments. Isolated compounds from M. oleifera such as moringin, astragalin, and isoquercitrin, and identified compounds of M. oleifera such as phenolic acids and flavonoids (chlorogenic acid, gallic acid, ferulic acid, caffeic acid, kaempferol, quercetin, myricetin, (-)-epicatechin, and isoquercitrin) have been reported to have neuropharmacological activities. Therefore, these compounds may potentially contribute to the neuroprotective and anti-neuroinflammatory effects. More in-depth studies using in vivo animal models of neurological-related disorders and extensive preclinical investigations, such as pharmacokinetics, toxicity, and bioavailability studies are necessary before clinical trials can be carried out to develop M. oleifera constituents into neuroprotective agents.